Changements historiques à long terme du débit écoulé dans le Haut bassin du fleuve Sénégal - C. Faye (Proceedings of the International Association of Hydrological Sciences, 2021)
In this study, the flow trends on either side of the Manantali dam, in the upper Senegal River basin, were assessed. The assessment was carried out for the period 1970 to 2019 using the Sen slope and the Mann-Kendall test. The Mann-Kendall trend test was used to indicate the direction of the trends, while the Sen slope was used to assess the magnitude of the change. The results of the study showed that there was an upward trend in the flow of the Senegal River both annually and for every month upstream (Bafing-Makana station) and downstream (Bakel station) from the barrage. The strongest upward trend is noted in October on the upstream station with 4.12 m3/month and in September on the downstream station with 10.99 m3/month. In return, the weakest upward trend is observed in May on the upstream station with 0.07 m3/month and in August on the downstream station with 0.67 m3/month. The annual flow also showed a significant increase upstream (with a rate of 0.35 m3/year) and downstream (with a rate of 4.53 m3/year) with a confidence level of 99 %. The results of the study also showed that an increase in precipitation causes an increase in runoff, despite the construction of hydraulic structures.